“Evaluación del Trichoderma spp., como acondicionador de suelos cultivado con maíz (Zea mays L.), en la zona de Puebloviejo” - Yépez Macías, Cristian Carlos (2018)
VIII. SUMMARY The investigation was carried out in the properties of the farm La Libertad. Located in the km 4,5 in the road Puebloviejo-Catarama. The objective was to evaluate the effect of different dose of the biofertilizer Ecoflora, Biotamax and Trichotic in the cultivation of corn, determining its effect on the grain yield, population of microorganisms and economic interest. The hybrid ADV was sowed 9313 in parcels of 12 m2. They were carried out ten treatments with three repetitions. The treatments were distributed at random in a design of complete blocks. For the evaluation of stockings the test was used from Tukey to 5 % significance. During the cycle of the cultivation they were evaluated: height of plants, ear diameter, radical biomass, number of ears for plant, ear longitude, days to crop, days to flowwring, weight seed, yield for hectare and an economic analysis and population of microorganisms. The results showed that the highest yield was achieved applying Ecoflora 350 g/ha, 65% more with relationship to the witness. In a same way Ecoflora 350 g/ha presents the best utility. The populations of microorganisms indicate levels means of bacterias, celuloliticos and nitrogen fixers, in all the treatments; first floor in mushrooms, match solubilizador and actinomicete.